Culture, financial literacy, and SME performance in Ghana - Samuel Kwaku Agyei (Cogent Economics & Finance, 2018)
This study extends the literature on financial literacy and cultural (Catholicism or Protestantism) beliefs to SME performance in a developing economy setting. Two basic questions motivated the study: (1) does culture influence financial literacy?; and (2) does culture mediate the relationship between financial literacy and firm performance in Ghana? The results, from 300 randomly sampled SME-Owners and based on Ordinary Least Squares and Logit regressions, suggest that cultural values militate against financial knowledge acquisition. Furthermore, Protestant beliefs strengthen the probability that SMEs would take advantage of growth opportunities due to financial literacy. Thus, the study concludes that the relationship between financial literacy and SME growth is cultural-context dependent. The study recommends that (1) religious bodies should inculcate financial education in their teachings; (2) financial literacy training programmes for SME-Owners should be tailored to meet their needs; and (3) cultural beliefs of SME-Owners should be of prime consideration in designing financial literacy programmes.
Keywords: 330; culture; financial literacy; SME performance; Ghana